2017
DOI: 10.1111/ppa.12708
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and recombination analysis of sorghum isolates of Sugarcane yellow leaf virus

Abstract: Recombination has played an important role in evolution and genetic diversity of Sugarcane yellow leaf virus (SCYLV) isolates sequenced to date. This study found that three newly sequenced SCYLV sorghum isolates from the USA underwent intraspecies recombination. No statistical significance on probable progeny-parent relationships involving SCYLV sorghum isolates were found in possible interspecies recombination with 18 members of the Luteoviridae family. Sorghum isolates deposited in the GenBank database under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
2
11
0
3
Order By: Relevance
“…Such an interference of Indian strains as major and minor parents for Pakistan-originated recombinant strain highlight its potential to cross international borders 48 . Similar finding has previously been observed for another RNA virus (Yellow leaf virus) from Pakistan and India 49 . Potnetial reason for such a sharing of genetic material could be spectulative and may be attributed to an increased disease incidence rate and frequent disease outbreaks near borderline of these countries 50,51 .…”
Section: Discussionsupporting
confidence: 90%
“…Such an interference of Indian strains as major and minor parents for Pakistan-originated recombinant strain highlight its potential to cross international borders 48 . Similar finding has previously been observed for another RNA virus (Yellow leaf virus) from Pakistan and India 49 . Potnetial reason for such a sharing of genetic material could be spectulative and may be attributed to an increased disease incidence rate and frequent disease outbreaks near borderline of these countries 50,51 .…”
Section: Discussionsupporting
confidence: 90%
“…Varios autores han reportado un grupo exclusivo para cepas de Reunión (genotipo REU) (Wang et al, 2012;Chinnaraja et al, 2013;Amata et al, 2016;ElSayed et al, 2018). En este estudio secuencias de Reunión y Mauricio fueron agrupadas en un clúster, en el cual los dos aislamientos REU que resultaron homólogos entre sí compartieron 99.41 y 99.61% de identidad con dos secuencias de Mauricio: AJ491264.1 y AJ491263.1, respectivamente.…”
Section: Resultados Y Discusiónunclassified
“…WLYaV had the closest relationship with ScYLV (64.9% for full length nucleotide and 86.2% for deduced amino acid sequences of ORF3). When the full-length genome and ORF3 deduced amino acid sequences of 10 representative ScYLV isolates (Elsayed et al, 2017 ) were compared with WLYaV (Table S4 ), the identities were 63.7~65.3% and 85.7~86.2%, respectively, below the species demarcation thresholds (90%) in the family Luteoviridae (Domier, 2012 ; Simmonds et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…ScYLV, a member of the genus Polerovirus , family Luteoviridae , causes severe leaf symptoms in sugarcane and exhibits significant genetic diversity with two phylogroups (Elsayed et al, 2017 ). Sequences comparison and phylogenetic analyses of WLYaV with 10 representative isolates of ScYLV (Table S4 , Figure S3 ) indicated that WLYaV and ScYLV are distinct.…”
Section: Discussionmentioning
confidence: 99%